Identification and Endodontic Management of Middle Mesial Canal in Mandibular Second Molar Using Cone Beam Computed Tomography - Bonny Paul; Kavita Dube (Case Reports in Dentistry)
Endodontic treatments are routinely done with the help of radiographs. However, radiographs represent only a two-dimensional image of an object. Failure to identify aberrant anatomy can lead to endodontic failure. This case report presents the use of three-dimensional imaging with cone beam computed tomography (CBCT) as an adjunct to digital radiography in identification and management of mandibular second molar with three mesial canals.